Construing National and Ethnic Groups Under the Genocide Convention Through Soviet and Russian Narratives on the Ukrainian Identities - Maksym Vishchyk (Наукові записки НаУКМА: Юридичні науки)
Debates on the genocidal nature of Russian atrocities in Ukraine have uncovered various grey zones of the law on genocide. While most contemporary commentaries have focused on the essence and scope of the crime’s central element – the intent to destroy the group in whole or in part – little analysis has been dedicated to defining and understanding the alleged object of the destruction, i.e., protected groups themselves. Even beyond the Ukrainian context, this problem is endemic to contemporary doctrine and jurisprudence, providing a rather cursory or even contradictory analysis of the notions of protected groups seemingly without recourse to other fields studying human identities, such as anthropology. This article aims to address this lacuna by exploring the dichotomy between national and ethnic groups under the Genocide Convention through Soviet and Russian identity narratives. The article summarises the state of contemporary law and jurisprudence relevant to the definition of the protected groups, as well as associated gaps and inconsistencies. It further addresses challenging issues of the groups’ definition and delimitation through the lenses of modern anthropology, where the law is silent. The article stresses the importance of multidisciplinary and contextualised application of the legal concepts under the law of genocide in light of the meaning ascribed to them by other fields of study focusing on group identities and inter-group dynamics. Finally, the article applies relevant findings to the context of Soviet and further Russian narratives on the Ukrainian identities, illustrating the dichotomy between national and ethnic groups.